PENGARUH KEPERCAYAAN, KEPUASAN KONSUMEN, NILAI YANG DIPERSEPSIKAN, DAN KOMITMEN PADA LOYALITAS - , Rita Kurniawaty, SE.; , Prof. Dr. Basu Swastha Dharmmesta, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research investigates the effect of trust, satisfaction, perceived value and commitment of consumers on their loyalty. The research uses both high and low involvement product in the survey to test the proposed hypothesis. The method used in the research is multivariate data analysis using structural equation model and questionnaire as the research instrument. The result shows that the most important construct for consumersâ loyalty is perceived value. It has positive influence on commitment. It also positively influences consumer satisfaction then the satisfaction positively influences trust. However, the research does not prove that consumer satisfaction and trust have influence on loyalty and commitment. Nevertheless, commitment itself has positive influence on consumersâ loyalty.